Mechanobiology and Mechanotherapy of Adipose Tissue-Effect of Mechanical Force on Fat Tissue Engineering. Issue 12 (December 2015) - Yuan, Yi; Gao, Jianhua; Ogawa, Rei
Abstract : Summary: Our bodies are subjected to various mechanical forces, which in turn affect both the structure and function of our bodies. In particular, these mechanical forces play an important role in tissue growth and regeneration. Adipocytes and adipose-derived stem cells are both mechanosensitive and mechanoresponsive. The aim of this review is to summarize the relationship between mechanobiology and adipogenesis. PubMed was used to search for articles using the following keywords: mechanobiology, adipogenesis, adipose-derived stem cells, and cytoskeleton. In vitro and in vivo experiments have shown that adipogenesis is strongly promoted/inhibited by various internal and external mechanical forces, and that these effects are mediated by changes in the cytoskeleton of adipose-derived stem cells and/or various signaling pathways. Thus, adipose tissue engineering could be enhanced by the careful application of mechanical forces. It was shown recently that mature adipose tissue regenerates in an adipose tissue-engineering chamber. This observation has great potential for the reconstruction of soft tissue deficiencies, but the mechanisms behind it remain to be elucidated. On the basis of our understanding of mechanobiology, we hypothesize that the chamber removes mechanical force on the fat that normally impose high cytoskeletal tension. The reduction in tension in adipose stem cells triggers their differentiation into adipocytes. The improvement in our understanding of the relationship between mechanobiology and adipogenesis means that in the near future, we may be able to increase or decrease body fat, as needed in the clinic, by controlling the tension that is loaded onto fat.